Genital Exceptionalism Has No Place in the Law: Improving Transgender and Intersex Rights in the 21st Century - Lindsey M. Walker (Washington University Law Review, 2019)
This Note defines genital exceptionalism as the importance that society places on genitalia as the determinative variable in establishing an individual’s gender, regardless of the individual’s identity and gender performance. So understood, genital exceptionalism assumes a strict binary view of gender and insists that all genitalia must conform to what society deems “normal” for a male or a female. If a person identifies as a woman, dresses as a woman, and tells the world that she is a woman, genital exceptionalism would say she is still a male so long as she has male genitalia. Genital exceptionalism has no room for those who identify with a gender outside the male-female binary, such as genderqueer. Much like sex exceptionalism, which views non-normative sex and sexuality with disdain, genital exceptionalism treats non-normative genitalia with contempt. Thus, genitalia that are outside of the norm—either because they are ambiguous, as is the case for intersex people, or because they are the genitalia society associates with the sex opposite of that which the person is presenting—is bad and wrong, and should be discouraged by the law. Although genital exceptionalism is pervasive among all populations, this Note argues that when genital exceptionalism underlies decisions in law and policy-making, the transgender and intersex communities suffer the most. This Note will first highlight three areas of the law that best example the negative, destructive aspects of genital exceptionalism: (1) in laws that require transgender individuals to use the public restroom designated for persons with the genitalia possessed by the individual at birth, regardless of the individual’s actual gender identity; (2) in laws that require transgender individuals to undergo sex reassignment surgery in order to change their gender marker on identity documents, such as driver’s licenses or birth certificates; and (3) in the absence of legal prohibitions on performing genital-normalizing surgery on infant and minor intersex children. This Note will then argue that when genital exceptionalism is given a place in the U.S. legal system, the natural and unavoidable consequences are violations of constitutional rights, emotional and physical harm, and economic losses that society as a whole must bear. Finally, this Note will propose the following solution: because genital exceptionalism is the root of much of the harm that is inflicted upon both the transgender and intersex communities in the United States, it would be beneficial for activists from each of the two groups to join forces in advancing their causes. These activists should work together to educate lawmakers and members of the judiciary on genital exceptionalism and why it is so harmful. Ultimately, the goal of these activists should be to alter the U.S. legal framework so that it no longer promotes genital exceptionalism, by (1) overturning the discriminatory transgender bathroom laws; (2) no longer requiring proof of sex reassignment surgery in order to change the gender markers on identity documents; and (3) passing legislation that forbids the performance of genital-normalizing surgery on children before they are legally capable of providing consent.
Keywords: Genital exceptionalism; Transgender rights; Intersex rights; Bathroom bills; Right to privacy; Gender identity